Psychomotor Functioning of Students with Mild Intellectual Disability at a Younger School Age in the Opinion of Parents and Teachers - Magdalena Wójcik (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction: Knowledge about the regularities of psychomotor development and the factors differentiating children individually determine the effects of didactic and educational work. It is the parent's acceptance, interest and attention devoted to the child, as well as parental experiences and competences that will determine the awareness of the actual developmental possibilities of the child. The teacher has the right and duty to observe the child in a multifaceted manner, as well as the forms of his actions and activities. Research Aim: The aim of the study is to find out the opinions of parents and teachers on the psychomotor functioning of students with mild intellectual disabilities at a younger school age. Method: Due to the qualitative nature of the research, the research method used was an interview with the use of the auxiliary tool: Short Child Development Scale developed by Magdalena Chrzan-Dętkoś Results: Both parents and teachers evaluate children below their biological age, with smaller disproportions in the assessment visible among second-graders and mainly related to cognitive and emotional skills. Both parents and teachers evaluate motor development in a similar way, and it is the area that is the least disturbed in comparison to cognitive, emotional and speech development. Conclusion: Parents of children with mild intellectual disability are aware of their children's developmental delays, but the knowledge of cognitive development, proper communication and emotional development differs from the knowledge of teachers. This may be due to different observations of children's behavior at home, other forms of working, a lack of sufficient knowledge. Teachers pay more attention to the features of cognitive development important from the point of view of the effectiveness of educational interactions.